KECENDERUNGAN TEMATIS CERPEN ANAK DALAM HARIAN KOMPAS EDISI JANUARI-MARET 2012: KAJIAN SOSIOLOGI SASTRA - Monicha Ardi; Nurizzati Nurizzati; Bakhtaruddin Nasution (Jurnal Bahasa dan Sastra, 2013)
This research purposes to discribe the theme from short story Anak Harian Compas January-Februari edision and theme of Anak harian Kompas is related with propensity of children behavior. This research is qualitatived by descriptive method. The method is used to describe data about the theme and relation between the theme and children nowadays in Short Story Anak Harian Kompas, January–March 2013 Edision. Data is collected by using some steps. These are : (1) Reading the children short story from Harian Kompas. (2) Investigating as the format inventarisasi data. Base on analysis, it is found eight themes which is decsribed those themes with children nowadays. These are : (1) generosity(2) About a trust. (3) Miscommunication. (4) Responsibility and hard working. (5) Riko’s creativity. (6) The struggle of scavengers girl. (7) obtruding. (8) Shying with condition.